2009
DOI: 10.1080/10253890802309853
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stress-inducible extracellular Hsp72 on human neutrophil chemotaxis: A role during acute intense exercise

Abstract: We studied the physiological role of the 72 kDa extracellular heat shock protein (Hsp72, a stress-inducible protein) in modulating neutrophil chemotaxis during a single bout of intense exercise performed by sedentary women, together with various cell mechanisms potentially involved in the modulation. For each volunteer, we evaluated neutrophil chemotaxis and serum Hsp72 concentration before and immediately after a single bout of exercise (1 h on a cycle ergometer at 70% VO(2) max), and 24 h later. Both paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 41 publications
5
59
0
Order By: Relevance
“…Walsh et al (2001) were the Wrst to report that Hsp72 is also released into the blood during intense exercise (1 h at 70% of VO 2max ), and it is now well known that exercise intensity and duration aVects the serum levels of Hsp72 (Fehrenbach et al 2005). Previous studies in our laboratory have also reported increased levels of Hsp72 in the circulation of sedentary people 1 h after a single bout of moderate (55% VO 2max ; Ortega et al 2006) and intensive (70% VO 2max ) exercise together with increased neutrophil microbicide capacity (Ortega et al 2006) and chemotaxis (Ortega et al 2009), which suggest an important role for Hsp72 in the exerciseinduced immunomodulation. In the case of chemotaxis, the Hsp72-induced stimulation needs the participation of TLR-2, suggesting also an interaction of Hsp72 and neutrophils.…”
Section: Introductionmentioning
confidence: 59%
“…Walsh et al (2001) were the Wrst to report that Hsp72 is also released into the blood during intense exercise (1 h at 70% of VO 2max ), and it is now well known that exercise intensity and duration aVects the serum levels of Hsp72 (Fehrenbach et al 2005). Previous studies in our laboratory have also reported increased levels of Hsp72 in the circulation of sedentary people 1 h after a single bout of moderate (55% VO 2max ; Ortega et al 2006) and intensive (70% VO 2max ) exercise together with increased neutrophil microbicide capacity (Ortega et al 2006) and chemotaxis (Ortega et al 2009), which suggest an important role for Hsp72 in the exerciseinduced immunomodulation. In the case of chemotaxis, the Hsp72-induced stimulation needs the participation of TLR-2, suggesting also an interaction of Hsp72 and neutrophils.…”
Section: Introductionmentioning
confidence: 59%
“…Under normal physiological conditions, Hsp72 is expressed at low levels. However, a wide variety of pathological stressful stimuli can induce a marked increase in its intracellular synthesis [21] and extracellular release [22,23]. Inflammation also results in the release of eHsp72 [24] and high circulating levels of eHsp72 may reflect a ‘chronic low-grade inflammatory status’.…”
Section: Discussionmentioning
confidence: 99%
“…FM patients are more prone to C. albicans infections than HW [39], which seems consistent with the increased phagocytic and microbicidal capacities against C. albicans found in the neutrophils from our FM patients. This greater phagocytic and fungicidal capacity (together with a greater chemotactic capacity) of neutrophils could be mediated by the raised circulating concentration of NA and eHsp72 in the FM patients, since it has been reported that increased systemic levels of NA and eHsp72 mediate the stimulation of chemotaxis, phagocytosis and the fungicidal activities of neutrophils [22,40,41,42]. However, the FM group’s decreased latex bead phagocytic capacity (a less specific form of phagocytosis because it is not mediated by pre-opsonization through antibodies) is suggestive of an immunosuppression mediated by the less specific innate immune response carried out by neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…In this compartment, HSPs act as alert stress signals priming other cells, particularly those of the immune system, to avoid the propagation of the insult and favor resolution (1). Extracellular HSP70 has also been reported to increase microbicide capacity and chemotaxis of neutrophils (2,3), to enhance phagocytosis (4), and to modulate the response of monocytes to endotoxin (5). Overall, extracellular HSP70 has been associated with both immunostimulatory and immunosuppressive activities, depending on the cell context and on the microenvironment in which the protein exists (6).…”
Section: Introductionmentioning
confidence: 99%